Incorporation of the factor IX Padua mutation into FIX-Triple improves clotting activity in vitro and in vivo - Kao, Chung-Yang; Yang, Shu-Jhu; Tao, Mi-Hua; Jeng, Yung-Ming; Yu, I-Shing; Lin, Shu-Wha (Thrombosis and Haemostasis, 2013)
Using gain-of-function factor IX (FIX) for replacement therapy for haemophilia B (HB) is an attractive strategy. We previously reported a high-activity FIX, FIX-Triple (FIX-V86A/E277A/R338A) as a good substitute for FIX-WT (wild-type) in protein replacement therapy, gene therapy, and cell therapy. Here we generated a new recombinant FIXTripleL (FIX-V86A/E277A/R338L) by replacing the alanine at residue 338 of FIX-Triple with leucine as in FIX-Padua (FIX-R338L). Purified FIX-TripleL exhibited 22-fold higher specific clotting activity and 15-fold increased binding affinity to activated FVIII compared to FIXWT. FIX-TripleL increased the therapeutic potential of FIX-Triple by nearly 100% as demonstrated with calibrated automated thrombogram and thromboelastography. FIX-TripleL demonstrated a normal clearance rate in HB mice. The clotting activity of FIX-TripleL was consistently 2- to 3-fold higher in these mice than that of FIX-Triple or FIXR338L. Gene delivery of adeno-associated virus (AAV) in HB mice showed that FIX-TripleL had 15-fold higher specific clotting activity than FIX-WT, and this activity was significantly better than FIX-Triple (10-fold) or FIX-R338L (6-fold). At a lower viral dose, FIX-TripleL improved FIX activity from sub-therapeutic to therapeutic levels. Under physiological conditions, no signs of adverse thrombotic events were observed in long-term AAV-FIX-treated C57Bl/6 mice. Hepatocellular adenomas were observed in the high- but not the medium- or the lowdose AAV-treated mice expressing FIX-WT or FIX-Triple, indicating the advantages of using hyperfunctional FIX variants to reduce viral doses while maintaining therapeutic clotting activity. Thus, incorporation of the FIX Padua mutation significantly improves the clotting function of FIX-Triple so as to optimise protein replacement therapy and gene therapy.
Keywords: Coagulation factors; haemophilia therapy; animal models